2002
DOI: 10.1007/s00420-002-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exhaustion and related risk factors in employees in the manufacturing industry - a cross-sectional study

Abstract: Objectives: Vital exhaustion, a construct overlapping with burnout, is an independent risk factor for adverse health outcomes, including cardiovascular disease. We aimed to assess vital exhaustion in employees in the manufacturing industry and identify work characteristics associated with exhaustion. Methods: Cross-sectional study. A stratified, representative random sample of employees from a manufacturing plant for airplane parts and assemblies was invited (n=647), of whom 537 employees (83% accrual) volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 23 publications
2
47
1
2
Order By: Relevance
“…En segundo lugar y en relación con el tema que nos atañe, debemos resaltar que en la actualidad nos encontramos con una bibliografía llena de aportaciones referentes a la importancia del síndrome de Burnout en las profesiones sanitarias (médicos/as, enfermeros/as, auxiliares) 10,12,[26][27][28][29][30] . A pesar de ello, sigue existiendo gran disparidad de resultados en cuanto a las prevalencias del Burnout en general y de cada uno de sus tres componentes en particular.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En segundo lugar y en relación con el tema que nos atañe, debemos resaltar que en la actualidad nos encontramos con una bibliografía llena de aportaciones referentes a la importancia del síndrome de Burnout en las profesiones sanitarias (médicos/as, enfermeros/as, auxiliares) 10,12,[26][27][28][29][30] . A pesar de ello, sigue existiendo gran disparidad de resultados en cuanto a las prevalencias del Burnout en general y de cada uno de sus tres componentes en particular.…”
Section: Discussionunclassified
“…Otro punto en el que coincidimos con los expertos en el tema es en el papel que juegan los factores «estresantes» laborales 30,35 . La mayoría de los profesionales encuestados manifestaban claramente la existencia de conflictos en relación con estos factores, que pueden ser los responsables mayoritarios de su insatisfacción 5,23,32,33,36 .…”
Section: Discussionunclassified
“…Our group has previously suggested that vital exhaustion should be considered as an indicator of the breakdown of adaptation to a chronically stressful working environment. However, the question as to what extent an individual's intrinsic disposition contributes to the risk of exhaustion was left unanswered in our previous work (Schnorpfeil et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Excess fatigue and feelings of general malaise are among the most prevalent precursors of myocardial infarction and sudden cardiac death (Appels and Mulder 1988;Cole et al 1999;Kop et al 1994). Vital exhaustion is also associated with depression (Kopp et al 1998;Raikkonen et al 1996;van Diest and Appels 1991), type-D personality (Denollet 2000;Schmidt Pedersen and Middel 2001), and with perceived work stress (Schnorpfeil et al 2002). Our group has previously suggested that vital exhaustion should be considered as an indicator of the breakdown of adaptation to a chronically stressful working environment.…”
Section: Introductionmentioning
confidence: 99%
“…The study was part of a larger project as previously reported (Schnorpfeil et al, 2002). The ethic committee of the Swiss Federal Institute of Technology, Zurich, Switzerland, has formally approved the study protocol.…”
Section: Experimental Subjectsmentioning
confidence: 99%